Genome sizes of three species in the subtribe Carabina (Coleoptera: Carabidae). Issue 1 (21st August 2012) - Sota, Teiji; Konuma, Junji; Fujiwara, Mayuki; Shoguchi, Eiichi
Abstract Genome sizes of three species in the subtribe Carabina (Coleoptera: Carabidae: tribe Carabini) were estimated from nuclei of spermatozoa using a flow cytometry. The estimated haploid genome sizes were about 330 megabases (Mb) for Damaster blaptoides, about 280 Mb for Carabus uenoi and about 260 Mb for Carabus yamato.